Are new states more corrupt? Expert opinions vs. firms' experiences - Tamanna Adhikari; Michael Breen; Robert Gillanders (University College Dublin, UCD School of Economics, 2017)
We find that new states are perceived to be more corrupt even though businesses do not report more bribery in newer states. This is suggestive of an unearned, and likely high, reputational cost to being a new state. These findings hold over a number of specifications that include additional economic, historical, and geographic controls.
Keywords: D70; D73; D90; D02; F21; F23; 330; corruption; corruption perceptions; bribery; state age